Triggy Sum

Calculus Level 5

sin x 1 3 + sin 2 x 2 3 + sin 3 x 3 3 + \large \dfrac{\sin{x}}{1^3}+\dfrac{\sin{2x}}{2^3}+\dfrac{\sin{3x}}{3^3}+\cdots

What is the maximum value of the above expression?

π 3 36 \dfrac{\pi^3}{36} π 3 18 \dfrac{\pi^3}{18} π 3 18 2 \dfrac{\pi^3}{18\sqrt{2}} π 3 18 3 \dfrac{\pi^3}{18\sqrt{3}}

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Hassan Abdulla
May 9, 2018

let f ( x ) = k = 1 sin ( k x ) k 3 f ( x ) = k = 1 cos ( k x ) k 2 f ( x ) = k = 1 sin ( k x ) k k = 1 sin ( k x ) k is the Fourier series expansion of the function f ( x ) = π x 2 for x ( 0 , 2 π ) ) so f ( x ) = 1 2 x π 2 f ( x ) = 1 4 x 2 π 2 x + C // integrate both side f ( 0 ) = k = 1 1 k 2 = ζ ( 2 ) = π 2 6 C = π 2 6 f ( x ) = 1 4 x 2 π 2 x + π 2 6 f ( x ) = 1 12 x 3 π 4 x 2 + π 2 6 x + C // integrate both side f ( 0 ) = 0 C = 0 f ( x ) = 1 12 x 3 π 4 x 2 + π 2 6 x 1 4 x 2 π 2 x + π 2 6 = 0 3 x 2 6 π + 2 π 2 = 0 x 6 π ± 36 π 2 24 π 2 6 = π ( 3 ± 1 3 ) //critical points f ( π ( 3 + 1 3 ) ) = 1 12 π 3 ( 3 + 1 3 ) 3 π 3 4 ( 3 + 1 3 ) 2 + π 3 6 ( 3 + 1 3 ) = π 3 18 3 f ( π ( 3 1 3 ) ) = 1 12 π 3 ( 3 1 3 ) 3 π 3 4 ( 3 1 3 ) 2 + π 3 6 ( 3 1 3 ) = π 3 18 3 so the maximum value of the expression is π 3 18 3 \text{let } f\left( x \right) =\sum _{ k=1 }^{ \infty }{ \frac { \sin { \left( kx \right) } }{ { k }^{ 3 } } } \\ f^{ ' }\left( x \right) =\sum _{ k=1 }^{ \infty }{ \frac { \cos { \left( kx \right) } }{ { k }^{ 2 } } } \\ f^{ '' }\left( x \right) =\sum _{ k=1 }^{ \infty }{ \frac { -\sin { \left( kx \right) } }{ { k } } } \\ \sum _{ k=1 }^{ \infty }{ \frac { \sin { \left( kx \right) } }{ { k } } } \text{ is the Fourier series expansion of the function } f(x)=\frac { \pi -x }{ 2 } \text{ for } x\in (0,2\pi )) \\ \text{so } f^{ '' }\left( x \right) =\frac { 1 }{ 2 } x-\frac { \pi }{ 2 } \\ f^{ ' }\left( x \right) =\frac { 1 }{ 4 } x^{ 2 }-\frac { \pi }{ 2 } x+C \color{#D61F06} \text{ // integrate both side} \\ f^{ ' }\left( 0 \right) =\sum _{ k=1 }^{ \infty }{ \frac { 1 }{ { k }^{ 2 } } } =\zeta \left( 2 \right) =\frac { \pi ^{ 2 } }{ 6 } \Rightarrow C=\frac { \pi ^{ 2 } }{ 6 } \Rightarrow f^{ ' }\left( x \right) =\frac { 1 }{ 4 } x^{ 2 }-\frac { \pi }{ 2 } x+\frac { \pi ^{ 2 } }{ 6 } \\ f\left( x \right) =\frac { 1 }{ 12 } x^{ 3 }-\frac { \pi }{ 4 } x^{ 2 }+\frac { \pi ^{ 2 } }{ 6 } x+C\qquad \color{#D61F06} \text{ // integrate both side} \\ f\left( 0 \right) =0\Rightarrow C=0\Rightarrow f\left( x \right) =\frac { 1 }{ 12 } x^{ 3 }-\frac { \pi }{ 4 } x^{ 2 }+\frac { \pi ^{ 2 } }{ 6 } x\\ \frac { 1 }{ 4 } x^{ 2 }-\frac { \pi }{ 2 } x+\frac { \pi ^{ 2 } }{ 6 } =0\Rightarrow 3x^{ 2 }-6\pi +2\pi ^{ 2 }=0\Rightarrow x\frac { 6\pi \pm \sqrt { 36\pi ^{ 2 }-24\pi ^{ 2 } } }{ 6 } =\pi \left( \frac { \sqrt { 3 } \pm 1 }{ \sqrt { 3 } } \right) \color{#D61F06} \text{ //critical points} \\ f\left( \pi \left( \frac { \sqrt { 3 } +1 }{ \sqrt { 3 } } \right) \right) =\frac { 1 }{ 12 } { \pi }^{ 3 }\left( \frac { \sqrt { 3 } +1 }{ \sqrt { 3 } } \right) ^{ 3 }-\frac { { \pi }^{ 3 } }{ 4 } \left( \frac { \sqrt { 3 } +1 }{ \sqrt { 3 } } \right) ^{ 2 }+\frac { { \pi }^{ 3 } }{ 6 } \left( \frac { \sqrt { 3 } +1 }{ \sqrt { 3 } } \right) =\frac { -{ \pi }^{ 3 } }{ 18\sqrt { 3 } } \\ f\left( \pi \left( \frac { \sqrt { 3 } -1 }{ \sqrt { 3 } } \right) \right) =\frac { 1 }{ 12 } { \pi }^{ 3 }\left( \frac { \sqrt { 3 } -1 }{ \sqrt { 3 } } \right) ^{ 3 }-\frac { { \pi }^{ 3 } }{ 4 } \left( \frac { \sqrt { 3 } -1 }{ \sqrt { 3 } } \right) ^{ 2 }+\frac { { \pi }^{ 3 } }{ 6 } \left( \frac { \sqrt { 3 } -1 }{ \sqrt { 3 } } \right) =\frac { { \pi }^{ 3 } }{ 18\sqrt { 3 } } \\ \large \text{so the maximum value of the expression is }\frac { { \pi }^{ 3 } }{ 18\sqrt { 3 } }

I want to I me where the negative in step 3 went, it's not there in step 5.

jonathan nicholson - 2 years, 1 month ago

Log in to reply

f ( x ) = k = 1 sin ( k x ) k = k = 1 sin ( k x ) k = ( π x 2 ) = x π 2 f^{ '' }\left( x \right) =\sum _{ k=1 }^{ \infty }{ \frac { -\sin { \left( kx \right) } }{ { k } } }=-\sum _{ k=1 }^{ \infty }{ \frac { \sin { \left( kx \right) } }{ { k } } }=-\left ( \frac { \pi -x }{ 2 } \right )= \frac { x -\pi }{ 2 }

Hassan Abdulla - 2 years ago

max. value of f(x) tends to infinity as x tends to infinity since f(x) is a cubic equation with positive co-efficient of highest degree term?? why do we calculate local maxima and minima here??

Hrithik Thakur - 1 year, 8 months ago

Log in to reply

it's a periodic function so it's repeat it self

see step 4

Hassan Abdulla - 1 year, 8 months ago

It's fine now... Thanks

Hrithik Thakur - 1 year, 8 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...